ODF4, MAGEA3, and MAGEB4: Potential Biomarkers in Patients with Transitional Cell Carcinoma - Afsharpad, Mandana (Iran Biomed J, 2018)
BACKGROUND: This study aimed to evaluate the diagnostic value of outer dense fiber 4 (ODF4), melanoma-associated antigen A3 (MAGEA3), and MAGEAB4 mRNAs in transitional cell carcinoma (TCC), using a small amount of cell reverse transcriptase-polymerase chain reaction (RT-PCR) on urinary exfoliated cells. METHODS: We recruited a total of 105 suspected TCC patients and 54 sex- and age-matched non-TCC controls. The candidates’ genetic expression patterns were investigated with RT-PCR, while reverse transcription quantitative PCR was applied to quantify and compare each mRNA level between cases and control groups. RESULTS: The sensitivity of ODF4, MAGEA3, and MAGEAB4 RT-PCR was 54.8%, 63%, and 53.4%, whereas the specificity was 73.7%, 86%, and 94.7%, respectively. Combining ODF4, MAGEA3, and MAGEAB4 RT-PCR offered a relatively higher sensitivity (83.6%). CONCLUSION: RT-PCR with ODF4, MAGEA3, and MAGEAB4 on urinary exfoliated cells could provide clinicians with a promising method to improve TCC diagnosis, especially in the case of gross hematuria and catheterization. The method used here is non-invasive, simple and convenient, and unlike cytology, it does not rely directly on expert professional opinions. These features can be of particular importance to the management of TCC patients in whom regular and lifelong surveillance is required.